IMPLEMENTASI AKAD JUAL BELI PERSPEKTIF MADZHAB AL-SYAFI’I DAN KONTESTUALISASINYA PADA JUAL BELI DI PASAR TIRTAYASA SERANG - Alwani, Alwani; Pujiono, Pujiono (An Nawawi, 2022)
The location of this study is located in Tirtayasa Serang Bnaten Market, which is the reason the area is used as the object of research is because the market has a strategic place and neatly arranged, from trading places to vehicle parking lots, then researchers are interested in the implementation time of the Market that operates only on Wednesdays and Saturdays. This writing uses field research (field research) that is by jumping in the field or research location. Data collection techniques with interviews, observations, documentation. The data from this study consists of primary data and secondary data, and is then analyzed with qualitative descriptive research methods. From the results of field research, researchers get and obtain the fact of the implementation of buying and selling in accordance with Madzhab shafi'i, some people use as in Indonesian the word "thank you" as a form of acceptance. Regarding shighat, traders in Tirtayasa still use although not all, but practiced by some traders as did Mother Fatimah, a clothing merchant who still uses shighat (ijab and qabul) like the word "I sell this item to you" and then the buyer replied "I received goods from you".' But sometimes it is used if there are similar buyers using it. Then the use of Khiyar in buying and selling traders use it but if there are defective goods caused by the merchant, then the goods can be returned by the buyer to the merchant, while the defective goods are caused by the buyer, then the goods cannot be returned by the buyer to the merchant. In addition, regarding the use of buying and selling agreements there are those who use customary customs (Urf) but there are benefits of the habit, between sellers and buyers. The implementation of this research is the need for a buying and selling agreement in accordance with Madzhab Shafi'i in order to achieve buying and selling in accordance with the principles of fiqh science provisions in Madzhab Shafi'i, insyaaAlloh useful and blessings.